2013
DOI: 10.1007/978-3-642-37437-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Emotions Related to Privacy and Trust in Personalized Services

Abstract: Abstract. This study explores the dynamics of personalized services in online shopping, with regard to emotions, privacy and trust. The basic emotions of happiness and anxiety were chosen. A sample of 182 online shoppers was used to assess the effect of privacy and trust on their emotions through personalized services, and how these emotions ultimately affect their purchase intentions. The findings indicate that privacy affects anxiety while trust affects happiness, while both emotions have significant influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…Specifically, in the case of an unsuccessful personalized offer, users' negative emotions might not be affected because experienced users are able to find the product they need without assistance. In addition, this result can be attributed to the existence of other factors that have a stronger effect on emotion formulation, such as presentation timing, recommendation type (Ho et al 2011), or trust and anxiety (Pappas et al 2013). Our findings do not verify Valenzuela et al (2009), who found that self-customization might reduce the negative feelings that result from product customization.…”
Section: Summary Of Contributioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Specifically, in the case of an unsuccessful personalized offer, users' negative emotions might not be affected because experienced users are able to find the product they need without assistance. In addition, this result can be attributed to the existence of other factors that have a stronger effect on emotion formulation, such as presentation timing, recommendation type (Ho et al 2011), or trust and anxiety (Pappas et al 2013). Our findings do not verify Valenzuela et al (2009), who found that self-customization might reduce the negative feelings that result from product customization.…”
Section: Summary Of Contributioncontrasting
confidence: 84%
“…If personalization is properly presented to customers it might produce positive feelings, such as enjoyment (Pappas et al 2012); however, personalized features on a website can confuse or frustrate customers, making them skeptical about using this tool. Customers who are overloaded with information are likely to develop negative emotions ), especially if that information is based on their private data (Li et al 2011;Pappas et al 2013). Privacy violation is related to trust, a fundamental factor in online shopping.…”
Section: The Role Of Emotions On Formulating Shopping Behaviorsmentioning
confidence: 99%
“…Our results also show an interesting interplay between personality traits and different persuasive principles. For example, the interaction between the personality trait conscientiousness and the persuasive principle reciprocity shows that customers with a high need for cognitive processing will go through the central route of persuasion [10], meaning that they will carefully look at the argumentation within the online advertisements and consider the best options on merit (as seen in figure 3) [2,6]. In the case of reciprocity, either the receiver was getting extra benefits, or the contributor was getting something in return.…”
Section: Resultsmentioning
confidence: 99%
“…Online personalization is a new phenomenon, applied to websites of organizations that want to offer tailored content and services to their (prospective) customers, based on the data gathered from their customers' interactions with different services [10]. The design of an interactive system, such as a website, should be based upon an understanding of the cognitive abilities of the website users [4].…”
Section: Introductionmentioning
confidence: 99%
“…Setting them in a particular news cycle through enhanced recommendation algorithms would likely backfire, as their information needs are not uniform and constantly evolving. Meanwhile, it is argued that users also develop a negative perception when the information they are receiving is based on their private data [112,113]. Therefore, privacy concerns that emerge out of content personalization affect the habitual behavior of users negatively for availing personalized services.…”
Section: Discussionmentioning
confidence: 99%